PEMBERDAYAAN TRANSFORMASI DIGITAL KEPADA MASYARAKAT DALAM DUNIA TECHNOPRENEURSHIP - Alfannisa Fajrin; Rifky Akbar Vetian (ASOSIASI IDEBAHASA KEPRI, 2026)
Digital transformation has become a major catalyst for creating new opportunities in various sectors, including technopreneurship. This research aims to examine community empowerment strategies in the digital era and how technology can be integrated into technology-based entrepreneurial activities. This empowerment focuses not only on the use of digital devices but also on strengthening human resource capacity through training, digital literacy, and access to digital platforms that support technopreneurial activities. The method used in this research is a descriptive qualitative study using observation and interviews with small- to medium-scale technology entrepreneurs in urban and semi-urban areas. For example, Cake House Aurora is still a home-based business. They still use manual marketing methods, resulting in limited sales. However, increasing digital literacy and the success of technology-based businesses will help Cake House Aurora. Furthermore, empowerment initiatives through digital communities, business incubators, and cross-sector collaboration play a crucial role in accelerating technology adoption. Therefore, empowerment in digital transformation must be directed at developing an innovative, collaborative, and adaptive mindset to change. In conclusion, a digitally educated population has great potential to become resilient, creative, and competitive technopreneurs in the digital economy era.